"Our everything" the myth of Pushkin by the prism of Soviet dissident writers - Mikaelyan, Yulia (RUS (Sao Paulo), 2017)
Being one of the main symbols of the Russian culture, the figure of the poet Aleksandr Pushkin is of special importance for the Russian culture. In this article, we aim to give a brief overview of the Pushkin’s myth development throughout the 19th – 20th centuries and to analyze the approaches of three dissident writers, Joseph Brodsky (1940-1996), Andrei Sinyavsky (1925-1997) and Sergei Dovlatov (1941-1990), to the official Soviet Pushkin myth.